PERBANDINGAN KINERJA EKONOMI USAHATANI CENGKEH ANTARA VARIETAS ZANZIBAR DAN SIKOTOK - Azizah Amalia Azmar; Jumiati; Nadir (MAHATANI: Jurnal Agribisnis (Agribusiness and Agricultural Economics Journal), 2026)
The research aimed to: 1) analyze the production costs and revenue from clove farming varieties of Zanzibar and Sikotok; 2) assess the income of these clove farming varieties; 3) evaluate the feasibility and profitability of Zanzibar and Sikotok clove farming. The study used purposive sampling, selecting 10 clove farmers from both varieties. The analytical methods included examining production costs, assessing revenue, analyzing income, evaluating feasibility, and conducting profit analysis and t-test analysis: (1) production costs for Zanzibar variety clove farms were Rp. 1,103,373, while total costs for Sikotok clove farms were Rp. 1,026,341. Revenue from Zanzibar variety clove farms was Rp. 6,270,000, with a production of 66 kg per year. In contrast, revenue from Sikotok variety clove farming was Rp. 4,410,000, with a production of 63 kg. (2) The income from Zanzibar variety clove farming was Rp. 5,166,627, while income from Sikotok variety clove farming was Rp. 3,383,659. (3) The R/C ratio for Zanzibar variety was 5.6, indicating that income exceeds total costs (R/C ratio > 1). The R/C ratio for Sikotok variety was 4.2, also indicating that farming both varieties is feasible. The B/C ratio for Zanzibar clove farming is 5.6, showing that revenue exceeds total costs (B/C ratio > 1). Similarly, the B/C ratio for Sikotok clove farming is 4.6, confirming it also qualifies as B/C ratio > 1. Thus, both Zanzibar and Sikotok varieties of clove farming are deemed feasible and profitable. The independent t-test results show a significance value of 0.001, which is less than 0.05. The t-count for Zanzibar and Sikotok clove farming is 6.131, while the t-table value is 2.306, indicating that the t-count exceeds the t-table value.